Global numerical model for the evaluation of the geometry and operation condition effects on hollow cathode insert and orifice region plasmas - Korkmaz, Oğuz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Thermionic hollow cathodes have been widely used in wide variety of areas such as spacecraft electric propulsion systems, material processing and lasers for more than half a century as e cient electron sources. Especially in electric propulsion systems, hollow cathodes are being used as electron sources for propellant ionization and ion beam neutralization. Moreover, hollow cathode is also a promising candidate for utilization as a stand-alone propulsion system in microsatellites or nanosatellites due to its small physical size, low power consumption and ease of operation. On the other hand, the small geometry of the typical ori ced hollow cathodes make the plasma diagnostics di cult which is why numerical studies become important for understanding the driving physical processes behind their operation, and the e ects of the geometry and the operation parameters on cathode performance. In this thesis a global numerical model for the insert and ori ce plasma of a hollow cathode is presented where volume averaged plasma parameters are considered for both regions. The results of this study show that the developed model can be used for designing and sizing ori ced hollow cathodes as comparisons with the results of experimental and other numerical studies are in good agreement with the ones obtained from the developed model.
Keywords: Electric discharges.